Vaccination programme in India- the present status: a review - S., Gopalakrishnan; P., Sujitha (International Journal Of Community Medicine And Public Health, 2020)
Vaccines are substances that are used to provide immunity by stimulating the production of antibodies. Immunization is a process by which a person is made to develop resistance towards infectious diseases by using a vaccine. Immunization programme is one of the key interventions for protection of children from life threatening conditions, which are preventable. By this cost effective intervention program, morbidity and mortality due to vaccine preventable diseases has been drastically reduced. In India, immunization programme was introduced in 1978 as ‘Expanded Programme of Immunization’ (EPI) by the Ministry of Health and Family Welfare. In 1985 the programme was modified as ‘Universal Immunization Programme’ (UIP) implemented in a phased manner. Through this programme nearly 12 vaccines are provided to infants, children and pregnant women. Even though the UIP is expected to cover all the eligible children and pregnant women in the country, the overall vaccination coverage falls short of the expected targets in different geographical regions of the country. As per NFHS 4 data, Punjab had the highest and Nagaland had the lowest vaccination coverage and there is a huge gap between the urban and rural areas in India. Through this review article the authors are trying to trace out the history and evolution of the vaccination programmes and the present status of the programme in view of the various difficulties it faces in recent times, which can lead to outbreaks and re-emergence of already controlled vaccine preventable diseases.